2006
DOI: 10.1016/j.otohns.2005.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Endoscopic Sinus Surgery Failure: A Role for Radical Surgery?

Abstract: C-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 20 publications
1
21
1
3
Order By: Relevance
“…This was found to be insignificant statistically. In a retrospective study, Wynn and Har found a recurrence rate in patients with nasal polyps of 60% after 40 months of follow up 12. The lower rate in our study may be due to the shorter period of follow-up.…”
Section: Discussioncontrasting
confidence: 57%
“…This was found to be insignificant statistically. In a retrospective study, Wynn and Har found a recurrence rate in patients with nasal polyps of 60% after 40 months of follow up 12. The lower rate in our study may be due to the shorter period of follow-up.…”
Section: Discussioncontrasting
confidence: 57%
“…Kerrebijn et al performed it in 56 patients and reported relief of sinusitis with significant improvement in symptoms 13. Videler et al78, 79 reported significant improvements in symptoms and quality‐of‐life measures from Denker's procedure, and Wreesmann et al80 reported improvement of lower airway symptoms in asthmatic patients. Both suggested that radical surgery should be an option for patients who fail repetitive conservative functional surgery 78, 80…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic sinus surgery remains the gold standard for the treatment of chronic sinusitis [7], it appears to be a very effective method for the treatment of an upper eyelid fistula when it combined with excision of the fistular tract. Endoscopic surgery attempts to restore normal ciliary flow within the sinuses using minimal invasive surgery on the osteo-meatal unit [8], and can usually establish intranasal drainage of mucocoeles [9].…”
Section: Discussionmentioning
confidence: 99%